Efficiency, Profitability and Stability of Nepalese Commercial Banks (The Batuk, 2021)
Efficiency, profitability and stability become an area of emergent concern in the literature and the practice. This paper attempts to examine the efficiency, profitability and stability of the Nepalese commercial banks and shows the importance of banking activities rather than simply profit achieved. Descriptive and causal-comparative research designs are used and data are collected from the financial reports of respective banks and NRB reports during the period of 2011/12 to 2019/20 of 27 commercial banks with 243 observations. Descriptive statistics have been used to present quantitative data in a manageable form and the relationship between dependent and independent variables are examined using correlation, simple and multiple regression analysis. It is found a negative and significant relationship between bank efficiency and profitability; a positive and significant relationship between bank efficiency and stability. Perhaps, this paper may be the first attempt to examine the determinants of efficiency, profitability and stability of Nepalese commercial banks. It is expected this study will bring new insight into the banking field and would provide a framework and guidelines for future study in Nepalese financial sectors.